العوامل السوسيوثقافية لإدمان المرأة على المخدرات في المجتمع الجزائري - الربيعي كريمة (البليدة2- كلية العلوم الإنسانية و الإجتماعية, 2024)
عرفت المرأة الجزائرية في الأونة الأخيرة انحرافات اجتماعية تساوت بها والانحرافات التي كانت حكرا على الرجل سابقا، فأصبحت تتعاطى المخدرات وتدمن عليها شأنها شأن الرجل وهذا راجع لظروف وعوامل اجتماعية وثقافية أثرت في سلوك المرأة ودفعت بها لإدمان المخدرات، لذلك انطلقت دراستنا من التساؤل الرئيسي التالي الذي هدفنا من خلاله إلى التعرف على أهم هذه العوامل الاجتماعية والثقافية المرتبطة بإدمان المرأة على المخدرات، ومحاولة تفسير المشكلة تفسيرا علميا والكشف عن تبعياتها وما يترتب عنها من مشكلات اجتماعية أكثر تعقيدا، حيث كان التساؤل كالآتي: ماهي أهم العوامل الاجتماعياة والثقافية والنتائج المرتبطة بإدمان المرأة على المخدرات؟ ويندرج عن هذا السؤال الأسئلة الفرعية الآتية: كيف يمكن لطبيعة الضبط الأسري أن تكون لها علاقة بإدمان المرأة على المخدرات؟ هل الطبيعة العلاقات التي تقدمها المرأة في الواقع وفي العالم الاقتراضي علاقة بإدمانها على المخدرات؟ كيف يساهم إدمان المرأة على المخدرات في حدوث الجريمة الجنسية؟ حيث تمت ترجمت هذه الأسئلة إلى فرضيات قامت عليها هذه الدراسة: الطبيعة الضبط الأسري علاقة بإدمان المرأة على المخدرات. طبيعة العلاقات التي تقيمها المرأة سواء في الواقع أو في العالم الافتراضي تؤدي إلى إدمانها على المخدرات. يساهم الإدمان على المخدرات عند المرأة في حدوث الجريمة الجنسية. ومن أجل الوصول إلى نتائج علمية دقيقة تؤكد هذه الفرضيات أو تنفيها ارتأينا استخدام منهج دراسة الحالة والمنج الوصفي للبحث والتقصي في الموضوع، معتمدينا فيها على أداة أو تقنية الملاحظة كأداة مساعدة والمقابلة كتقنية أساسية في جمع المعطيات من مجموعة من المختصين، و15 حالة من نساء المدمنات على المخدرات اللاتي تم استخراجها باعتماد على المعاينة القصدية باعتبارها أحد أنواع المعاينات غير الاحتمالية التي يتم استخدامها في حالة عدم وجود قاعدة بيانات عن مجتمع الدراسة كما تمت هذه الدراسة في كل من جامعة البليدة 2 الإقامة الجامعية للبنات والمركز الوطني الاستقبال فتيات ونساء ضحايا العنف ومن هنا في وضع صعب ببوسماعيل ولاية تيبازة، وكذا مركز العلاج والوقاية من المخدرات والإدمان عليها بمستشفى فرانس فاتون بولاية البليدة، في الحدود الزمنية الممتدة من 2022/02/12 إلى غاية 2022/07/25. وقد خلصت هذه الدراسة إلى النتائج التالية: أغلب النساء المدمنات على المخدرات يتراوح ستهن بين 19 و 28 سنة، كما ظهر أن أغلبهن مستواهن التعليمي ثانوي ومستواهن الاقتصادي متوسط، وأن فئة العازبات منهن والماكنات في البيت من أكثر توجها نحو تعاطي المخدرات والإدمان عليها. بينت الدراسة أيضا علاقة الأسرة بإدمان المرأة على المخدرات، والذي يظهر من خلال عدم قدرت الأسرة على التحكم وضبط سلوك بناتهن الأسباب عديدة منها الأساليب التنشيئية الخاطئة أو المشاكل الأسرية من تفكك أو تصدع وغيرها. أبرزت الدراسة دور المخالطة والعلاقات الاجتماعية التي تقيمها المرأة في الواقع أو في العالم الافتراضي في انحرافها وإدمانها للمخدرات. كما توصلنا أيضا في هذه الدراسة إلى أن المرأة المدمنة على المخدرات تقع وترتكب كثير من الانحرافات الجنسية كالبغاء الزنا، الخيانة الزوجية والوقوع ضحية التحرش الجنسي الاغتصاب والاختطاف وغيرها من الجرائم الأخرى كالسرقة، الاحتيال والتسول. وقد توصلنا أيضا إلى ارتباط مشكلة المخدرات عند المرأة بمشكلات اجتماعية أخرى أكثر تعقيدا مثل ظهور مشكلة الأطفال غير الشرعيين الإجهاض، مشكلة الطلاق والهجر. Recently, Algerian women have known social deviations that were equal to those that were previously exclusive to men. They began to use drugs and become addicted to them, just like men. This is due to social and cultural circumstances and factors that affected women's behavior and pushed them to become addicted to drugs. Therefore, our study began from the following main question, which we aimed for. Through it, we will identify the most important social and cultural factors associated with women's addiction to drugs, and attempt to explain the problem scientifically and uncover its dependencies and the more complex social problems that result from it. The question was as follows: What are the most important social and cultural factors and outcomes associated with women's drug addiction? This question includes the following sub-questions: How might the nature of family control relate to a woman's drug addiction? Does the nature of the relationships that women have in reality and in the virtual world have anything to do with their addiction to drugs? How does women's drug addiction contribute to sexual critne? These questions were translated into hypotheses on which this study was based: The nature of family control has a relationship with womer's drug addiction. The nature of the relationships that women have, whether in reality or in the virtual world, leads to their addiction to drugs. Drug addiction in women contributes to sexual crime. In order to reach accurate scientific results that confirm or deny these hypotheses, we decided to use the case study approach and the descriptive approach to research and investigate the subject, relying on the tool or technique of observation as an auxiliary tool and the interview as a basic technique in collecting data from a group of specialists, and 15 cases of women addicted to alcohol. Drugs that were extracted based on purposive sampling as it is one of the types of non-probabilistic sampling that is used in the absence of a database on the study population. This study was also carried out at the University of Blida 2 - the university residence for girls - and the National Center for the Reception of Girls and Women Victims of Violence and Those in a Difficult Situation in Bousmail, Tipaza Province, as well as the Center for Treatment and Prevention of Drugs and Addiction at the France Fanon Hospital in Blida Province, within a period of 12 months. /02/2022 until 07/25/2022. This study concluded the following results: Most of the women addicted to drugs are between 19 and 28 years old. It also appeared that most of them have a secondary education level and an average economic level, and that the group of single women who stay at home are more inclined towards drug abuse and addiction. The study also showed the family's relationship with women's addiction to drugs, which appears through the family's inability to control and regulate their daughters' behavior for many reasons, including wrong upbringing methods or family problems such as disintegration or rifts, among others. The study highlighted the role of socialization and social relationships that women maintain in reality or in the virtual world in their deviance and drug addiction. We also found in this study that women addicted to drugs: commit many sexual deviations, such as prostitution, adultery, marital infidelity, and falling victim to sexual harassment, rape, kidnapping, and other crimes such as theft, fraud, and begging. We have also found that the drug problem among women is linked to other more complex social problems, such as the emergence of the problem of illegitimate children, abortion, divorce, and abandonment.
Keywords: الجرائم الجنسية للمرأة; المخدرات; المجتمع الجزائري; الإدمان